2020
DOI: 10.1039/c9gc04401a
|View full text |Cite
|
Sign up to set email alerts
|

Using dialkyl amideviaforming hydrophobic deep eutectic solvents to separate citric acid from fermentation broth

Abstract: The separation of citric acids was realized by utilizing hydrophobic deep eutectic solvents (DESs), which were formed by using N,N-dibutylacetamide as a hydrogen acceptor and citric acid as the hydrogen bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…DOA was synthesized according to the reported literature . The 1 H NMR spectrum of DOA showed that it was successfully synthesized (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DOA was synthesized according to the reported literature . The 1 H NMR spectrum of DOA showed that it was successfully synthesized (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the DEO as a HBD for the extraction of boron from aqueous solutions was reported . The DOA as HBA via forming HDESs to recover citric acid from the fermentation broth was developed . On the other hand, Cai et al pointed out that diamide had a strong ability to extract Fe­(III) in the HCl solution, and Allal et al used DEO to extract titanium from chloride media .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…14−16 However, the relatively complicated synthesis process and expensive raw chemicals limit their application in large-scale industries. 17,18 Recently, deep eutectic solvents (DESs), also called analogues of ILs, as new-generation solvents, have been developed at a fast pace due to their green character, biodegradability, tunability, low cost, and simple preparation, compared to conventional organic solvents and ILs. 19 they were widely used in the extraction of metals and organic compounds.…”
Section: ■ Introductionmentioning
confidence: 99%